La Russie et le dégel arctique - Pierre Thorez (Bulletin de l’Association de Géographes Français)
Climatic change offers new possibilities to exploit natural resources of the Extreme North, which had been partly abandonned. Geopolitical and economic challenges have led the government to promote a new law on the North Sea route, an essential tool to develop Arctic Russia and a potential route for domestic and international transit.